Blockchain-powered grids: Paving the way for a sustainable and efficient future - Ullah, Nazir; Al-Rahmi, Waleed Mugahed; Alblehai, Fahad; Fernando, Yudi; Alharbi, Zahyah H.; Zhanbayev, Rinat; Al-Adwan, Ahmad Samed; Habes, Mohammed (Elsevier Ltd, 2024)
Blockchain technology can potentially be a bedrock for the energy record-keeping system. This study examined several critical factors that affect users’ intention to accept Blockchain technology for the Smart grid. The proposed model is based on the Technology Organization Environment framework, which is examined using Structural Equation Modelling. Based on the study findings, it has been indicated that the relative advantage shows a significant effect and matters the most during the Blockchain technology adoption in the Smart grid. The innovativeness, cost saving, and regulatory support also significantly influence the intention to use the Blockchain technology. The innovativeness and traceability show a significant influence on upper management support. The traceability shows a substantial impact on cost savings. However, innovativeness shows an insignificant effect on cost savings. The traceability and competitive pressure do not affect the intention to use the Blockchain technology. This study has extended the Technology Organization Environment theory, which predicts the organizational behavior to adopt the Blockchain technology for the Smart grid. We argue that the finding provides insights to guide the industry to deliver the best practice on the Blockchain technology. The study findings suggest that experts would recognize innovative technology free of effort to raise the determined aids for improving the traditional energy system. Though there are some limits, theoretical and practical implications are justified based on the findings.